Implementing safe abortion in Ghana: "We must tell our story and tell it well". (30th October 2018) - Chavkin, Wendy; Baffoe, Peter; Awoonor‐Williams, Koku
Abstract: In the first years of the new century, the Ministry of Health/Ghana Health Service determined to reduce abortion‐associated morbidity and mortality by increasing access to safe care. This was accomplished by interpreting Ghana's restrictive law so that more women qualified for legal services; by framing this effort in public health terms; by bundling abortion together with contraception and postabortion care in a comprehensive package of services; and by training new cadres of health workers to provide manual vacuum aspiration and medical abortion. The Ministry of Health/Ghana Health Service convened medical and midwifery societies, nongovernmental organizations, and bilateral agencies to implement this plan, while retaining the leadership role. However, because of provider shortages, aggravated by conscientious objection, and because many still do not understand when abortion can be legally provided, some women still resort to unsafe care. Nonetheless, Ghana provides an example of the critical role of political will in redressing harms from unsafe abortion. Abstract : Starting in 1994, Ghana reinterpreted its abortion law to broaden access and reduce unsafe provision. Implementation of services has been aided by task sharing, multisector cooperation, and political will.